Desmoid-Type Fibromatosis of the Mesentery: Report of a Sporadic Case with Emphasis on Differential Diagnostic Problems - Giovanni Li Destri; Maria Jessica Ferraro; Martina Calabrini; Monica Pennisi; Gaetano Magro (Case Reports in Medicine)
Desmoid-type fibromatosis is a rare mesenchymal neoplasm with local aggressiveness. The incidence of desmoid-type fibromatosis is 2–5/million/year with intra-abdominal fibromatosis, such as that which is reported in this clinical case, occurring only in 12–18% of cases. After having analyzed the pathogenetic hypotheses of desmoid-type fibromatosis, the authors point out that the diagnosis of this disease, especially in the intra-abdominal form, is often late, specifically when highly demolitive interventions are needed or when the limits of radical surgery have been exceeded. In the clinical case reported, the tumor was infiltrating both ileus and sigma. The authors consider the differential diagnosis of desmoid-type fibromatosis, especially with GISTs, with regard to both the radiological preoperative diagnostic and histological studies on the surgical specimen. Radical surgical excision is not always, for this disease, a sign of healing; in fact, even when the resection margins are negative, the incidence of recurrence is between 13 and 68%. The average time of recurrence is between 15 and 24 months; in this case report, the patient, who has not been subjected to complementary therapies, is tumor-free for over 30 months since surgery; his prognosis may be satisfactory if we consider the negativity of resection margins, which in any case remains the most important prognostic factor.